Low-Code Platform in The Analysis and Evaluation System for Epidemic Simulation Exercises - Robert WASZKOWSKI; Tadeusz NOWICKI (Communications of International Proceedings, 2021)
This paper describes the method for planning, collecting data and determining indicators for the purpose of evaluation of the training audience in computer assisted exercises of sanitary inspectors connected with the epidemic of food-borne diseases. The training audience evaluation method takes into account all phases of simulation exercises. The paper also presents an approach to defining, calculating and presenting the key performance indicators. It also discusses the detailed post-exercise analysis module (After Action Review). Authors refer also to the results based on two simulation exercises held in Warsaw in 2014.
Keywords: Food-Borne Diseases; Computer Assisted Exercises; CAX; Decision Support System; Business Process; Aurea BPM